Kajian Kerusakan Taman Hutan Raya (Tahura) di Indonesia melalui Pengendalian Pencemaran Lingkungan - Hamid, Abdul (Journal of Industrial Process and Chemical Engineering (JOICHE), 2024)
Forest Parks (Tahura) are vital conservation areas for the preservation of biodiversity and ecological functions in Indonesia. However, various human activities have caused significant damage to these areas. This study aims to assess the level of damage in several Tahura in Indonesia and evaluate the environmental pollution control strategies that have been implemented. The methods used include literature studies and secondary data analysis from various reliable sources. The results of the study indicate that damage in Tahura is caused by factors such as deforestation, illegal logging, and environmental pollution. Effective control strategies involve community participation, law enforcement, and ecosystem rehabilitation. An integrated approach is needed to ensure the sustainability of Tahura in Indonesia.